Pacopampa'05 Archaeological Project: Regional progress and correlations - Seki, Yuji (2017)
This article presents the results of the first season of archaeological fieldwork conducted at the site of Pacopampa, Cajamarca, by the Pacopampa Archaeological Project, which is organizad by the San Marcos University and the Japanese Nacional Museum of Ethnology. The data recovered from excavations, cleaning, and topographic mapping, allow us to confirm the prior chronology (of two phases) and suggest a third latest phase (Final Formative). Most of visible constructions correspond to the second phase (Pacopampa II). In addition, two construction sub-phases have been defined within this phase, while no structure have been clearly defined to the first phase (Pacopampa I). The ceramic patterns indicate strong linkages with archaeological sites located in the southern region ofCajamarca like Huacaloma and Kuntur Wasi. Nonetheless, radiocarbon dates put into question the chronological considerations obtained after observation of ceramics.